China's Policy to Close Borders to Prevent the Spread of the Second Wave of Covid-19 Virus - Elyta, Elyta; Rahmaniah, Syarifah Ema; Ramdani, Hendra (Universitas Muhammadiyah Yogyakarta, 2021)
At the beginning of 2020, the world was shocked by the outbreak of Covid-19, which was known to have originated from Wuhan. The increase in cases of local transmission in China's border region with Russia has sparked new concerns. In writing this paper, the author uses data collection methods with literature studies from journals and electronic books, including data from trusted websites through internet searches in the form of soft files that can support the paper's explanation. From the results of this paper, the reader can see that it is divided into several essential points explaining how China's policy to close the border in Russia to prevent the spread of the Covid-19 Virus in their country, first, how the procedures carried out by China in tightening checks on Russian borders. And Second, knowing how China monitors its citizens by using cell phones.